Utilizing Patient-Reported Outcomes to Assess the Impact of Complex Medical Disorders in Children. - Rodday, Angie Mae. (2017)
Abstract: Medical advances have extended survival for many conditions that were previously fatal in childhood. As a result of their underlying medical condition, children often experience decreased health-related quality of life (HRQL). In addition, parent caregivers, who often play a central role in the child's medical care, face newfound demands. Understanding the impact of complex medical conditions on children and their families will lead to better provision of care and improved health outcomes. The objectives were (1) to assess the relationship between child HRQL and parent emotional functioning among children undergoing hematopoietic stem cell transplant (HSCT); (2) to determine whether the child's HRQL predicts future healthcare utilization among children with chronic respiratory insufficiency (CRI); and (3) to develop custom physical functioning short forms and explore scale scores and preliminary psychometric properties among children with CRI who are at risk for decreased physical functioning. First, we utilized structural equation modeling (SEM) and linear regression modeling to assess the relationship between child HRQL and parent emotional functioning among 258 parent-child dyads undergoing pediatric HSCT. Both parent-proxy and child report were used to collect child HRQL. These analyses adjusted for child age. Second, we used negative binomial regression modeling to determine the relationship between parent-proxy report of child HRQL and total healthcare contact days in the 6-month window following the HRQL assessment among 120 children with CRI. This included inpatient days and days with emergency department or outpatient visits. These analyses adjusted for child age, physician-rated clinical severity, and years enrolled in a care coordination program. For the third dissertation objective, we developed two custom parent-proxy physical functioning short forms that targeted the lower range of functioning using pediatric item banks from the Patient Reported Outcomes Measurement Information System (PROMIS). We explored the initial validity and psychometric properties of these custom short forms in 57 children with CRI. Results from the SEM analysis revealed that our conceptual model that linked generic child HRQL to child HSCT-related worry, and then to parent emotional functioning provided a better fit than the conceptual model that placed child HSCT-related worry before generic child HRQL in relation to parent emotional functioning. Both the linear regression models and SEMs demonstrated relationships between child emotional functioning, child HSCT-related worry, and parent emotional functioning. However, there were some differences by parent-proxy and child raters. In the second project, three-quarters of children with CRI had any healthcare utilization and 32% were hospitalized during the 6-month window. We found that lower levels of child global HRQL and general health were both associated with more total healthcare contact days and inpatient days compared with those with better global HRQL and general health status, even after adjustment for clinical and demographic characteristics. Results from the third project showed that physical functioning scores were three standard deviations lower in children with CRI than in the general pediatric population. Preliminary psychometric validity was shown for the custom short forms, but many children still scored at the lowest end of the scale, and items about assistive devices proved inadequate in this sample. These collective results help give a better understanding of the experience of children with complex medical conditions and their families. We observed associations between child emotional functioning, child HSCT-related worry, and parent emotional functioning in the HSCT population. We observed high levels of healthcare utilization and decreased physical functioning among children with CRI. However, we also found opportunities to use patient- (or parent-proxy) reported outcomes to help identify patients who are at increased risk for negative health outcomes. Based on this, we can provide tailored clinical or psychosocial interventions that can improve health outcomes, reduce healthcare utilization, and provide better quality care.; Thesis (Ph.D.)--Tufts University, 2016.; Submitted to the Dept. of Clinical & Translational Science.; Advisor: Susan Parsons.; Committee: Norma Terrin, Robert Graham, and Laurel Leslie.; Keyword: Health sciences.